Thrombin and Cancer: From Molecular Basis to Therapeutic Implications - Franchini, Massimo; Mannucci, Pier Mannuccio (Seminars in Thrombosis and Hemostasis, 2012)
The relationship between cancer and thrombosis has been recognized for nearly 150 years. Although the mechanisms underlying this association are not completely understood, there are increasing evidences suggesting a pivotal role of thrombin in cancer biology. This review will focus on the most important pathways by which thrombin may affect cancer growth and dissemination. In addition, the potential role of congenital (i.e., hemophilia) and pharmaceutical (i.e., antithrombotic agents) anticoagulation in cancer incidence and survival will be investigated through the analysis of the published experimental and clinical studies.
Keywords: thrombin; cancer; hemophilia; anticoagulant